Pterygia are indicators of an increased risk of developing cutaneous melanomas. Issue 4 (26th August 2017) - Crewe, Julie M; Threlfall, Tim; Clark, Antony; Sanfilippo, Paul G; Mackey, David A
Abstract : Aim: To investigate whether pterygium is an indicator of an increased risk of cutaneous melanoma (CM). Methods: A matched-cohort study, using linked health administrative data sets to identify all hospital-treated pterygium in Western Australia (WA) between 1979 and 2014. We identified pterygium cases from hospital diagnosis and/or procedure International Classification of Diseases 9th revision (ICD-9) and 10th revision (ICD-10) codes and matched cases by age, sex and residential postcode to WA Electoral Roll controls with no known history of pterygium. Both cohorts were linked to the WA Cancer Registry and the WA Deaths Registry. Results: 23 625 people had pterygium treatment (64% male) in WA hospitals. The median age for pterygium diagnosis and/or treatment was 49 years (range 14–96). There were significantly more CM cases in the pterygium cohort compared with the control cohort (1083 vs 874; p<0.001). In a logistic regression analysis, there was a 24% increase in the odds of developing a CM in the pterygium cohort, compared with controls, after controlling for other predictors (OR 1.24, 95% CI 1.1 to 1.4). The incident rate ratio (IRR) of a malignant CM diagnosis was 20% greater in people who had treatment for a pterygium compared with controls (IRR 1.2, 95% CI 1.0 to 1.4). Conclusion: The presence of a pterygium indicates a significantly increased risk of developing a CM. Eye care providers who see patients with developing pterygia should advise these patients of this increased risk and recommend regular skin surveillance.